Recovery Monitoring for Substance Use Treatment in Ontario: Outcome Results from a Feasibility Assessment. Issue 3 (September 2016) - Rush, Brian; Chau, Nancy; Rotondi, Nooshin Khobzi; Tan, Felicia; Detfurth, Elida
ABSTRACT: Objectives: : The assessment of health outcomes of people participating in substance abuse treatment is considered an important element of performance measurement to complement controlled trials of clinical efficacy. We aimed to assess the feasibility of an outcome monitoring system for substance use treatment services in Ontario with a particular focus on the ability of a comprehensive tracking system and measures to determine change over time on relevant outcomes. Method: : A total of 148 clients aged 16 and over were prospectively recruited at two treatment programs for baseline interview and a detailed follow‐up tracking protocol. A group of 117 were located to determine 3 and 6 monthstatus. Outcomes were measured across multiple health and social domains as well as utilization and cost of health care and justice‐related services. Results: : There was a significant improvement in several indicators of substance use, including abstinence. Results also showed a significant decrease in severity over time in the areas of risk behaviour, crime and violence, and stress as well as overall indices of Life Problem Prevalence, and environmental risks to recovery. Overall quality of life improved. There was a reduction in health care utilization and justice involvement and an overall reduction in costs associated with these services. Conclusions: : Study findings confirmed the success of the client tracking process and the diverse set of measures in a sub‐set of programs where full implementation was possible, thus illustrating the value of scaling up routine outcome monitoring in other substance abuse treatment organizations or treatment systems. Abstract : Objectif : L'évaluation des résultats de santé des personnes participant au traitement de la toxicomanie est considérée comme un élément important dans la mesure de résultats en complément des essaies cliniques contrôlés. Nous avons cherché à évaluer la faisabilité d'un système de suivi des résultats dans les services de traitement de la toxicomanie en Ontario, en mettant un accent particulier sur la capacité d'un système de suivi complet pour retracer et mesurer les changements au fil du temps sur les résultats pertinents. Méthode: : Un total de 148 clients âgés de 16 ans et plus ont été recrutés de manière prospective dans deux programmes de traitement pour une entrevue de référence et un protocole de suivi détaillé. Un groupe de 117 ont été localisés pour déterminer des statuts de 3 et 6 mois. Les résultats ont été mesurés par rapport aux coûts et leur utilisation dans de multiples domaines de santés, de services sociaux, ainsi que des services liés à la justice. Résultats: : Il y a eu une amélioration significative dans plusieurs indicateurs de la consommation de substances, y compris l'abstinence. Les résultats ont également démontré une diminution significative de la gravité au fil du temps dans des domaines connexes, tels la criminalité, la violence, le stress, de meilleurs indices de vie globale et moins de risques environnementaux menant au rétablissement. En général, il y a eu une nette amélioration de la qualité de vie. Il y a eu une réduction de l'utilisation des soins de santé et des démêlés avec la justice ainsi qu'une réduction globale des coûts associés à ces services. Conclusions: : Les résultats des études ont confirmé le succès du processus de suivi des clients et l'ensemble des diverses mesures dans un sousensemble de programmes où la mise en œuvre complète était possible, illustrant ainsi la valeur de l'élargissement de suivi des résultats de routine dans d'autres organismes de traitement de la toxicomanie ainsi que les systèmes de traitement des abus.